The effect of interstitial hydrogen on the electronic structure of the B2 FeAl alloy - Gonzalez, Estela Andrea (2007)
The electronic structure and bonding in a B2 Fe-Al alloy with and without hydrogen as an interstitial atom were studied within the framework of the density functional theory and the findings compared with previous results in Fe an Al. The hydrogen absorption turns out to be a favorable process. The hydrogen was found near an Al octahedral site, the Al-H distance being shorter than that of Fe-H. The density of states (DOS) curves show several peaks below the d metal band which is made up mostly of hydrogen based states (>50% H 1s) while the metal contribution includes mainly s- and p-orbitals. An electron transfer of nearby 0.14 e- comes from the metal to the H. The overlap population values reveal metal-metal bond breaking, the intermetallic bond being the most affected. The H bond mainly with the Al atoms and the reported Fe-H overlap population is much lower than that corresponding to FePd alloys and BCC Fe. The changes in the overlap population show the Fe-Al bond is weakening nearly 53% after H absorption, while the Fe-Fe bond is only weakened 23%. © 2007 Wiley-VCH Verlag GmbH & Co. KGaA.